Injury potential of herbicide combinations on XtendFlex® cotton. (6th October 2021) - Samples, Chase Allen; Vieira, Bruno C.; Irby, Jon Trenton; Reynolds, Daniel; Catchot, Angus; Kruger, Greg R.; Dodds, Darrin M.
Abstract: XtendFlex® technology from Bayer allows growers to apply glyphosate, glufosinate, and dicamba POST to cotton. Since the evolution and spread of glyphosate-resistant weed species, early POST applications with several modes of action have become common. However, crop injury potential from these applications warrants further examination. Field studies were conducted from 2015 to 2017 at two locations in Mississippi to evaluate XtendFlex® cotton injury from herbicide application. Herbicide applications were made to XtendFlex® cotton at the three- to six-leaf stage with herbicide combinations composed of two-, three-, and four-way combinations of glyphosate, glufosinate, S -metolachlor, and three formulations of dicamba. Data collection included visual estimations of injury, stand counts, cotton height, total mainstem nodes, and nodes above whiteflower at first bloom. Data collection at the end of the season included cotton height, total mainstem nodes, and nodes above cracked boll. Visual estimations of injury from herbicide applications were highest at 3 d following applications containing glufosinate + S -metolachlor (36% to 41% injury) and glufosinate + S -metolachlor in combination with dicamba + glyphosate (39% to 41% injury), regardless of the dicamba formulation. Crop injury decreased at each rating interval and dissipated by 28 d following applications (P = 0.3748). Height reductions were present at first bloom and at the end of the season (P < 0.0001), although cotton yield was unaffected (P = 0.2089), even when injury at 3 d after application was greater than 30%. Results indicate that growers may apply a variety of herbicide tank mixtures to XtendFlex® cotton and expect no yield penalty. Furthermore, if growers are concerned with cotton injury after herbicide applications, the use of glufosinate in combination with S -metolachlor should be approached with caution in XtendFlex® cotton.